Smart hybrid wind-solar street lighting system fuzzy based approach: Case study Istanbul-Turkey - Wadi, Mohammed; Shobole, Abdulfetah; Tur, Mehmet Rida; Baysal, Mustafa; Wadi, Mohammed; Shobole, Abdulfetah Abdela (Institute of Electrical and Electronics Engineers Inc., 2018)
In this paper, fuzzy-based control approach is proposed to control the street lighting systems depending on solar and wind renewable energy sources. The light intensity is controlled according to the battery level and the speed of the wind. Fuzzy Logic Control (FLC) is an efficient technique for solving complex problems with little mathematical equations. The proposed fuzzy controller is designed with MATLAB. The proposed street lighting controller depending on the utility, making the efficient utilization of renewable energy such as solar and wind energy which is very necessary in this energy crisis world and the arising of the environmental pollution concerns. In Turkey, the demand for electric power is growing year after year so; this paper suggests a methodology to cut the electricity bill for the lighting of highways. To show effectiveness and savings of the proposed approach, it is applied to a small section of the lighting system of the environmental highway - in Turkish Çevre Yolu-in Istanbul. © 2018 IEEE.
6th International Istanbul Smart Grids and Cities Congress and Fair, ICSG 2018 -- 25 April 2018 through 26 April 2018 -- -- 137884
Keywords: Fuzzy Logic Control (FLC); High-Pressure Sodium (HPS); Hybrid Wind-Solar; lamps; Light Emitting Diode (LED); Photovoltaic (PV); Renewable Energy; Smart Street Lighting